Social adaptation status of Syrian refugee physicians living in Turkey - Furkan Dağcioğlu, Basri; Baydar Artantaş, Aylin; Keskin, Ahmet; Karataş Eray, İrep; Üstü, Yusuf; Uğurlu, Mehmet (Central European Journal of Public Health, 2020)
OBJECTIVES: Since the beginning of the civil war in Syria, over 3.5 million Syrians have fled to Turkey. Considering the massive burden of healthcare service needs of this population, the Turkish government has launched an initiative as employing Syrian doctors to provide health services to their citizens in Refugee Health Centres. In this study, we aimed to explore the social adaptation status of Syrian physicians living in Turkey using a structured questionnaire and the Social Adaptation Self Evaluation Scale (SASS). METHODS: Between November 2016 and April 2018, 799 physicians who participated in "Syrian Physicians' Adaptation Training" were enrolled in the study and underwent a structured questionnaire that questioned socio-demographic data and the SASS. The participants were divided into two groups as having poor and normal/high SASS scores. The binary SASS groups were compared with some demographic data. RESULTS: The median SASS score of the respondents was found as 43 (min. 10, max. 60, IQR 10) which can be accepted as normal. In the binary grouping, it was seen that 107 (13.39%) participants had poor social adaptation, whereas 692 (86.61%) participants had normal or high social adaptation scores. The physicians who were certain about not going back to Syria had significantly higher SASS scores. CONCLUSION: The social adaptation scores of the Syrian physicians were considerably high. The adaptation status was found to be associated with some characteristics like living in Turkey for a long time and having pre-knowledge about the Turkish healthcare system.
Keywords: Sýrie; Refugees; Adaptation, Psychological; uprchlické tábory; Syria; Humans; primární zdravotní péče; Social Adjustment; Primary Health Care; dostupnost zdravotnických služeb; Female; dospělí; lidé; Health Services; Turecko; Adult; kulturní kompetence; Health Services Accessibility; ženské pohlaví; Male; sociální přizpůsobení; lékaři; adaptace psychologická; Turkey; uprchlíci; Cultural Competency; mužské pohlaví; Physicians; Refugee Camps; zdravotnické služby